From Stock Bottle to Vaccine: Elucidating the Particle Size Distributions of Aluminum Adjuvants Using Dynamic Light Scattering - Shardlow, Emma; Mold, Matthew; Exley, Christopher (Frontiers in Chemistry, 2017)
The physicochemical properties of aluminum salts are key determinants of their resultant adjuvanticity in vivo when administered as part of a vaccine. While there are links between particle size and the efficacy of the immune response, the limited literature directly characterizing the PSD of aluminum adjuvants has stymied the elucidation of such a relationship for these materials. Hence, this comparative study was undertaken to monitor the PSD of aluminum adjuvants throughout the process of vaccine formulation using DLS. A significant proportion of the stock suspensions was highly agglomerated (>6.5µm), although a large degree of disaggregation was observed upon the dilution of all materials into saline. Adju-Phos® yielded the largest particles in this diluent (4251±137nm); however, the higher affinity of BSA for the surface of Alhydrogel® resulted in a comparable size being observed for both commercial adjuvants when this protein was included in the formulation. These results suggest that the PSD of aluminum adjuvants is greatly influenced by dilution and the degree of protein adsorption experienced within the vaccine itself. The size of the resultant antigen-adjuvant complex may be important for its immunological recognition and subsequent clearance from the injection site.